(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2005)
The results of a biostratigraphic study on the Upper Triassic-Lower Jurassic carbonate platform sediments are outlined. Three stratigraphic successions cropping out in different areas were analysed: Monte Cefalo, (Aurunci Mts, southern Latium), Costa dei Frascari (Matese, northern Campania) and Monte Meta (Gran Sasso d’Italia, Abruzzi). The study of microfossil assemblages composed of benthic foraminifers and calcareous algae allowed identification of four biozones and one subzone. From the bottom upwards, the biostratigraphic units are: the Triasina hantkeni and Griphoporella curvata Zone; the Thaumatoporella parvovesiculifera Zone; the Palaeodasycladus mediterraneus Zone; the Valvulinidae and Rivulariaceae Zone; and the Orbitopsella Subzone. Besides, the lower part of the Costa dei Frascari section was referred to the portion of the Norian below the first occurrence of the Triasina hantkeni and Griphoporella curvata. These sediments are characterized by a rich assemblages mostly composed of pseudoudoteaceans algae, echinoderm remains, chaetetids and large gastropods. Microbiostratigraphic study of the Upper Triassic-Lower Jurassic sediments highlighted a similar succession of bioevents in all the sections analysed allowing precise bio- and chronostratigraphic correlations to be made. In contrast, the paleoecological data obtained from biofacies analysis combined with lithological features observed in coeval units point to different depositional environments, reflecting time and space variation within the context of a single, large carbonate platform. In fact, both sedimentation, and the observed associations of organisms, were controlled by chemical-physical factors connected to variations in water energy and water circulation. Instead, in other cases tectonics and subsidence seem to have played an essential role.